Origin of the early Albian oceanic anoxic event 1b in the western tethys (Piobbico core, central Italy) and north Atlantic (ODP Leg 171b site 1049c): calcareous nannofossil evidence. - D. Tiraboschi; E. Erba (Federazione italiana di scienza della terra, 2007)
The mid-Cretaceous greenhouse climate represents the most extreme warmth of the past 300 My, characterized by intense volcanism and increased ocean crust production. Moreover, the mid-Cretaceous is associated with oceanic anoxic events (OAEs), periods of elevated carbon buriaI in marine sediments. Calcareous nannoplankton were sensitive to changes in temperature, fertility, and chemistry of surface waters. Consequently, abundance and composition of nannofossil assemblages are used to reconstruct paleoclimatic fluctuations and the functioning of the ocean/atmosphere system. Specifically, calcareous nannofloras are used for characterization of the earliest Albian OAE1b in order to assess the role of paleoclimatic changes leading to possible perturbations of surface water masses as triggers of anoxia. Oceanic Drilling Program (ODP) Site 1049C (Blake Nose) recovered Aptian to Eocene sediments. The upper Aptian – lower Albian sequence consists of marls and calcareous marls interrupted by a prominent black shale interval (46 cm thick), that has been identified as the local expression of OAE 1b. Calcareous nannofossils were investigated every 20 cm in the upper Albian – lower Albian sediments and the early Albian OAE1b interval was sampled at high-resolution (1 cm). A similar sampling was applied to the coeval interval in the Piobbico core, drilled in the Umbria-Marche Basin (central Italy). In both sections nannofossils are well preserved and the dominant species are W.barnesiae, R. asper, B. costans, Z. erectus, D.rotatorius, L. carniolensis. The warm-water taxa (R.asper and Z.diplogrammus) increase in abundance and temperature index shows warmer conditions within OAE 1b. This result is consistent with the oxygen stable isotope record, suggesting a significant warming at the onset of OAE1b.The meso-eutrophic taxa (Z.erectus, D.rotatorius and B.costans) increase in abundance 50 cm before OAE1b in the Piobbico core. and 2 meters before OAE 1b at Site 1049C. Within black shales the fertility taxa and nutrient index are ...